1988
DOI: 10.1136/vr.123.8.201
|View full text |Cite
|
Sign up to set email alerts
|

Stress in cattle assessed after handling, after transport and after slaughter

Abstract: Blood samples were collected from unstressed cattle and from cattle undergoing handling stress, transport stress and slaughter. The blood was analysed for ACTH, cortisol, thyroxine stimulating hormone, tri-iodothyronine (T3) and catecholamine concentrations, and for haematocrit, total plasma protein, plasma lipid, lactate and glucose concentrations. Compared to control values handling significantly increased T3, cortisol, lipid and lactate concentrations. Compared to handling, transport stress was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
93
6
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(115 citation statements)
references
References 0 publications
12
93
6
2
Order By: Relevance
“…Studying the relationship between behaviour and the hypothalamus-pituitary-adrenal (HPA) axis activity (Cole et al, 1988;Mitchell et al, 1988) allows a more precise detection of stress than mere observation . Till date feedback-free sampling methods for cortisol assays have been developed and validated for milk (Fukasawa et al, 2008), saliva (Pérez et al, 2004;Weston, 2009), faeces (Morrow et al, 2002;Kahrer et al, 2006) and urine (Morrow et al, 2000).…”
Section: Significance Of Hr and Hrv As Non-invasive Stress Parametersmentioning
confidence: 99%
“…Studying the relationship between behaviour and the hypothalamus-pituitary-adrenal (HPA) axis activity (Cole et al, 1988;Mitchell et al, 1988) allows a more precise detection of stress than mere observation . Till date feedback-free sampling methods for cortisol assays have been developed and validated for milk (Fukasawa et al, 2008), saliva (Pérez et al, 2004;Weston, 2009), faeces (Morrow et al, 2002;Kahrer et al, 2006) and urine (Morrow et al, 2000).…”
Section: Significance Of Hr and Hrv As Non-invasive Stress Parametersmentioning
confidence: 99%
“…Studies measuring the impact of human-directed activities on ungulates on a physiological base are, so far, mostly limited to livestock (e.g. Mitchell et al 1988, Dalin et al 1992, Bristow and Holmes 2007 or captive animals (e.g. Abeyesinghe et al 1997, Carragher et al 1997, to specific situations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Transport stress first activates the hypothalamic-adrenal cortex and then sympatheticadrenal-medulla (Mitchell et al, 1988) and alters the concentrations of a series of hormones, such as CRH, GnRH, TH, and ACTH. Numerous studies have shown that stress-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis plays an important role in inhibiting the hypothalamic-pituitary-gonadal (HPG) axis (Cevik et al, 2004;Chand and Lovejoy, 2011).…”
Section: Introductionmentioning
confidence: 99%